Mastering Microsoft Exchange Server 2016 - Leonard, Clifton; Svidergol, Brian; Wright, Byron; Meloski, Vladimir (Sybex, a Wiley brand, 2016)
A bestselling Exchange Server guide, updated for the 2016 release 'Mastering Microsoft Exchange Server 2016' is the gold-standard reference for system administrators and first-time users alike.